The impact of experimental pain on shoulder movement during an arm elevated reaching task in a virtual reality environment. Issue 18 (20th September 2021) - Dupuis, Frédérique; Sole, Gisela; Wassinger, Craig A.; Osborne, Hamish; Beilmann, Mathieu; Mercier, Catherine; Campeau‐Lecours, Alexandre; Bouyer, Laurent J.; Roy, Jean‐Sébastien
Abstract: Background: People with chronic shoulder pain have been shown to present with motor adaptations during arm movements. These adaptations may create abnormal physical stress on shoulder tendons and muscles. However, how and why these adaptations develop from the acute stage of pain is still not well‐understood. Objective: To investigate motor adaptations following acute experimental shoulder pain during upper limb reaching. Methods: Forty participants were assigned to the Control or Pain group. They completed a task consisting of reaching targets in a virtual reality environment at three time points: (1) baseline (both groups pain‐free), (2) experimental phase (Pain group experiencing acute shoulder pain induced by injecting hypertonic saline into subacromial space), and (3) Post experimental phase (both groups pain‐free). Electromyographic (EMG) activity, kinematics, and performance data were collected. Results: The Pain group showed altered movement planning and execution as shown by a significant increased delay to reach muscles EMG peak and a loss of accuracy, compared to controls that have decreased their mean delay to reach muscles peak and improved their movement speed through the phases. The Pain group also showed protective kinematic adaptations using less shoulder elevation and elbow flexion, which persisted when they no longer felt the experimental pain. Conclusion: Acute experimental pain altered movement planning and execution, which affected task performance. Kinematic data also suggest that such adaptations may persist over time, which could explain those observed in chronic pain populations. Abstract : Acute experimental pain alters movement planning and execution. Kinematic data suggest that motor adaptations may persist over time, which could explain those observed in chronic pain populations.